Leaf anatomy and essential oil characters of Cinnamomum pauciflorum Nees. - a potential spice crop from North-East India - Subhan C Nath, Akhil Baruah, (Journal of Spices and Aromatic Crops, 2006)
The anatomy and essential oil characters of leaf of Cinnamomum pauciflorum, a new promis-ing source of cinnamon was studied. Eighteen components accounting for 99.8% of the totaloil were identified by GC analysis of the oil. Cinnamaldehyde was the major component inthe oil.